Synthesis and Characterization of Carbonaceous Materials for Medical Applications: A Comprehensive Review - Ebenezer C. Nnadozie; Kennedy I. Ogunwa; Vitalis I. Chukwuike; Onyinyechukwu O. Nnadozie; Charles Ehikhase (BioMed)
Carbonaceous materials have gained significant attention in recent years for their various applications in the field of medicine and biotechnology. This comprehensive review explores the synthesis and characterization of carbon-based materials and their potentials in various medical applications. The paper delves into the methods of fabrication of carbon-based nanoparticles, such as carbon nanotubes, biochar, and graphene, while highlighting their unique properties. Characterization techniques, such as microscopy, spectroscopy, and surface analysis, are discussed to provide insights into the chemical and structural properties of these materials. Furthermore, the review examined their wide-ranging medical applications, encompassing tissue engineering, drug delivery, biosensing, and imaging, showcasing the versatility and promising contributions of carbonaceous materials in the healthcare industry. The review outlines the current challenges and prospects in the field, emphasizing the growing significance of carbon-based materials as valuable tools in advancing medical science and technology, as well as public health.